Sclerosing Angiomatoid Nodular Transformation of the Spleen: Analysis of Clinical and Pathological Features in Five Cases - Shao, Huijiang; Lu, Baochun; Shen, Zhihong; Liu, Fang (Frontiers in Surgery, 2021)
Objective: We aimed to summarize the clinical and pathological features of sclerosing angiomatoid nodular transformation (SANT) in spleen among five cases. Methods: Five cases (male: 3; female: 2; mean age: 47.6 yrs) with sclerosing angiomatoid nodular transformation (SANT) confirmed by pathological analysis between July 2010 and November 2019 in our hospital were included in this study. The clinical data, imaging and pathological data were analyzed retrospectively. Results: Three patients were manifested as mild abdominal pain or discomfort, while the other two were symptom-free. Two patients received ultrasonography (US) and all patients underwent computerized tomography (CT) scan in our hospital. The typical “spoke wheel” pattern was seen in two cases and central calcification was detected in one case on CT scans. All patients indicated peripheral enhancement around the SANT lesion during the arterial phase. Open or laparoscopic splenectomy was performed for treatment. No patient showed recurrence in the follow-up. The pathological characteristics of our cases were in line with those of previous literatures. Conclusions: Peripheral enhancement around the SANT lesion during the arterial phase should be taken into consideration for the diagnosis of SANT as an imaging sign on CT scans. Special attention should be paid to the splenic integrality during the laparoscopic approach, due to the probability of malignancy and the fragility of spleen.